Flame Atomic Absorption Spectrometric Determination of Pb, Cd, and Cu in Pinus nigra L. and Eriobotrya japonica Leaves Used as Biomonitors in Environmental Pollution - Kaya, Gokce; Ozcan, Cemile; Yaman, Mehmet (Springer, 2010)
The assessment of trace metal pollution in Gaziantep city-Turkey has been studied using plant leaves of Pinus nigra L. and Eriobotrya japonica as biomonitor. The concentrations up to 3,056 mg Pb kg(-1) in the needles of Pinus nigra L., and 367 ng Cd g(-1) in the leaves of Eriobotrya japonica were determined. The observed Cu concentrations were in range of 1.6-7.1 mg kg(-1). The Pb, Cd, and Cu levels in soils were determined to be in the range of 17-602, 0.142-0.656, and 12-38 mg kg(-1), respectively. It was concluded that Pinus nigra L. can be considered as both biomonitor of atmospheric Pb pollution and hyperaccumulator plant.
Keywords: Pinus nigra L.; Eriobotrya japonica; Atomic absorption; Metals